2019
DOI: 10.2339/politeknik.481762
|View full text |Cite
|
Sign up to set email alerts
|

Odunun Yüzey Pürüzlülüğünün ve Adezyon Direncinin Yapay Sinir Ağları ile Tahmini

Abstract: ÖZMobilya ve dekorasyon elemanlarının üretiminde kullanılan ağaç malzemelerin yüzey pürüzlülüğünün ve adezyon direncinin belirlenmesi, nihai ürünün kalitesinin değerlendirilmesi bakımından çok önemlidir. Bu makalede ilk olarak, odun türü, kesme yönü ve zımpara kağıdı türünün yüzey pürüzlülüğü üzerine etkilerini incelemek için yapay sinir ağı (YSA) ile yüzey pürüzlülüğü tahmin modeli geliştirilmiştir. Daha sonra, vernik türü, odun türü, kesme yönü ve yüzey pürüzlülüğünün adezyon direnci üzerine etkileri YSA ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…There are as many neurons in the input layer as there are data coming from the outside. Neurons operating in the input layer pass the information they collect directly to the hidden layer without modifying it [24]. The input units X1, X2, and X3 shown in Figure 1 represent information used to train, test, and validate the network.…”
Section: Input Layermentioning
confidence: 99%
“…There are as many neurons in the input layer as there are data coming from the outside. Neurons operating in the input layer pass the information they collect directly to the hidden layer without modifying it [24]. The input units X1, X2, and X3 shown in Figure 1 represent information used to train, test, and validate the network.…”
Section: Input Layermentioning
confidence: 99%
“…The ANN approach has been widely employed in wood science to model input-output relationships. ANN applications to wood science include analyzing moisture in wood (Avramidis and Wu 2007), predicting fracture toughness (Samarasinghe et al 2007), classifying wood veneer defects (Castellani and Rowlands 2008), wood recognition (Khalid et al 2008), optimization of process parameters in oriented strand board manufacturing (Özşahin 2012(Özşahin , Ozsahin 2013, predicting the bonding strength of wood joints (Bardak et al 2016), determination of optimum power consumption in wood machining (Tiryaki et al 2016), prediction of formaldehyde emission (Akyüz et al 2017), and prediction of surface roughness and adhesion strength of wood (Özşahin and Singer 2019). These studies have shown that the ANN approach produces highly successful results.…”
Section: Introductionmentioning
confidence: 99%